Book Publishers and Libraries: Historic Partners Facing a Disruptive Technology - Allen, Tom (Maine Policy Review, 2013)
The explosion of digital materials and e-readers has disrupted the historic partnership between book publishers and libraries. Tom Allen explains that the new business models required for more widespread e-lending will necessarily involve compromises. He suggests that e-lending pilot projects between individual publishers and libraries are a promising development.